Media Digital sebagai Distraksi Loyalitas Iman pada Remaja Katolik dalam Berelasi dengan Allah di Tengah Pluralisme Agama di Indonesia (Pusat Riset dan Inovasi Nasional, 2026)
The study aims to analyze the role of digital media as a distracting factor affecting the faith loyalty of Catholic adolescents in their relationship with God amid religious pluralism in Indonesia. The development of digital media has transformed how adolescents understand, express, and live out their faith, while simultaneously presenting both opportunities and ambivalent challenges. This research employs a qualitative approach using a library research method, analyzing various theological, sociological sources, and Church documents. The findings indicate that digital media can serve as a broad and participatory space for expressing faith, but it also has the potential to create distractions in three main dimensions: cognitive, affective, and practical. Cognitively, adolescents experience confusion in understanding faith teachings due to the diversity of information available. Affectively, there is a shift in orientation from a relationship with God toward the pursuit of emotional gratification in digital spaces. Practically, there is a decline in engagement in concrete religious practices. Within the context of religious pluralism, this complexity intensifies and influences the formation of adolescents’ faith identity. This study also finds that digital media does not only have negative impacts but also holds positive potential as a means of deepening faith when used critically and reflectively. Therefore, the role of the Church is essential through contextual, dialogical, and integrative pastoral accompaniment combined with critical digital literacy. Through this approach, adolescents are expected to integrate their digital experiences into a more mature, authentic faith life rooted in a deeper relationship with God.